A Lamp Controller via Missed Calls Based On The Microcontroller AVR AT90S2313 - Jazi Eko Istiyanto; Andik Dwi Kuntoro (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
Missed calls have a potential for low-cost control and monitoring of a remote instrumentation system as compared to SMS (Short-Message Service) and DTMF (Dual-Tone Multiple Frequencies). The design of an instrumentation system model in which a set of lamps can, remotely, be turned on/off just by issuing a set of unanswered calls and the programming of the AT90S2313 microcontroller to serve the purpose of controlling and status monitoring of a set of six lamps (AC bulbs) are presented in this paper. Two cellular phones are used: one as the calling phone, and the other as the receiving end (the transceiver). The transceiver is attached to the microcontroller circuitry. The calling phone issues two sets of RINGs and the transceiver is programmed to disregard any RING. The first set of RINGs is interpreted as a command to select one of the six lamps, then the second set of RINGs constitutes a command to turn the selected lamp on/off. This is possible because the cellular system records the number of RINGs before a call qualifies as a missed call.The system has successfully been built, tested, and proven to work well. The limitation is, apart from the GSM signal availability, the inability of the current system to verify/authenticate the calling phone number.